Pengaruh Opini Audit, Kualitas Auditor, dan Komite Audit terhadap Ketepatan Waktu Pelaporan Keuangan - Widya Maharani Nur Wulan; Arif Hartono; Ika Farida Ulfah (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research aims to determine the influence of audit opinion, auditor quality, and audit committee on the timeliness of financial reporting. The population in this study was 75 mining sector companies for the 2018-2022 period which were listed on the Indonesia Stock Exchange (BEI). The data used in this research is secondary data sourced from company annual reports which are accessed via the official IDX website (www.idx.co.id) and the websites of each mining sector company. The independent variables used in this research consist of audit opinion, auditor quality, and audit committee, while the dependent variable is the timeliness of financial reporting. The number of samples used was 57 companies with a research period of 5 years. The sampling technique in this research used a purposive sampling technique. This type of research uses a quantitative approach. Research data processing uses SPSS version 27 with logistic regression analysis method. Based on the results of the analysis that has been carried out, the results show that the audit opinion and auditor quality variables have an effect on the timeliness of financial reporting, while the audit committee variable has no effect on the timeliness of financial reporting. Simultaneous testing shows that the variables audit opinion, auditor quality, and audit committee have an influence on the timeliness of financial reporting.